DECISION-MAKING IN THERAPEUTIC GROUPS - Fatout, Marian F (Groupwork, 2020)
The major focus in the group literature on decision-making processes has been in the area of task groups. Relatively little attention has been given to these processes in relation to therapeutic groups. There are linkages between the stages of group decision making and group development which can add understanding and knowledge to practice in therapeutic groups. Publisher’s note: We are now putting all back issues of Groupwork on line. Articles in this issue have been scanned to pdf files as viable original typesetting files no longer exist. Though they may not look it, these files are to some extent searchable. This issue was published nearly 30 years ago. We have stated author professional details as received at time of publication.